2019
DOI: 10.2196/14404
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Interventions to Improve Adherence to Antiretroviral Therapy in People Living With HIV: Systematic Review and Meta-Analysis

Abstract: BackgroundElectronic health (eHealth) is increasingly used for self-management and service delivery of HIV-related diseases. With the publication of studies increasingly focusing on antiretroviral therapy (ART) adherence, this makes it possible to quantitatively and systematically assess the effectiveness and feasibility of eHealth interventions.ObjectiveThe purpose of this review was to explore the effectiveness of eHealth interventions on improving ART adherence in people living with HIV. The effects of diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 76 publications
0
22
0
Order By: Relevance
“…(64,65). Innovative approaches will also be needed to 1) account for disparities in access to technology (both digital devices and internet access), and 2) monitor the e cacy and safety of medication use if regular testing and viral load monitoring are limited (63,(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…(64,65). Innovative approaches will also be needed to 1) account for disparities in access to technology (both digital devices and internet access), and 2) monitor the e cacy and safety of medication use if regular testing and viral load monitoring are limited (63,(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…A review found mobile phone–based interventions for adolescent sexual and reproductive health (SRH) in LMIC to be an effective way to reach young people, increase health knowledge, and achieve behavior change and noted a need for more research on security, confidentiality, and structural issues such as phone access [ 12 ]. More generally, several systematic reviews have shown that there is substantial evidence for the utility of mobile phone reminders to improve antiretroviral therapy adherence for people living with HIV in East Africa [ 14 , 15 ]. Studies in Uganda suggest that SMS text messaging is also a feasible and acceptable platform to support tuberculosis medication adherence [ 16 , 17 ] and testing [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was no group with daily and monthly messages, based on studies that showed that these sending frequencies are less effective than the weekly or biweekly ones, and the text messages used in the intervention groups are based on the conceptual framework of social support (12,(18)(19) . The messages sent did not inform the diagnosis of HIV infection, respecting the patients' privacy.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, some systematic reviews have shown that interventions based on medical consultations, nursing consultations, telephone calls, text messaging, financial incentives and behavioral therapy have improved adherence to ART, but none has carried out an assessment from an economic and epidemiological perspective, aiming to demonstrate how these interventions interfere in the long term in the incidence of new cases (3)(4)9,(12)(13)(14) . In this sense, nonmedication and cost-effective interventions, from an economic point of view, such as sending text messages, can help maintain adherence throughout ART without dispensing high costs to the health system and with easy applicability for large populations regardless of their location and facility to the health system (7,(14)(15) .…”
Section: Introductionmentioning
confidence: 99%